PENGARUH KEPEMIMPINAN, MOTIVASI, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN JUMANTONO KABUPATEN KARANGANYAR - Utami, Setyaningsih Sri (Universitas Slamet Riyadi, 2010)
ABSTRACT The objective of the research is to analyses (1) the impact of leadership towards employee’s performance, (2) the impact of motivation towards employee’s performance, (3) the impact of communication towards employee’s performance, (4) the impact of work environment towards employee’s performance, (5) variable the most influencing towards employee’s performance. The analysis result shows the regression equation is : Y = -3,675 + 0,417X1 + 0,213X2 + 0,148X3 + 0,572X4 + e. ; (1) The t test variable of leadership, motivation, communication, and work environment with p value 0,018; 0,041; 0,178; and 0,005; so the variables of leadership, motivation, and work environment have a positive anf significantly effect on the employee’s performance, but communication variable has not significantly effect on the employee’s performance. (2) Work environment variable have most dominant influence to the employee’s performance, because t-value of work (3,040) are bigger than another variables. (3) Coefficient determination test is Adjusted R2 = 0,792. The conclusion of the research that: (1) Leadership had a positive and significance effect to the employee’s performance of the Jumantono Subdistrict in Karanganyar Regency, (2) Motivation have a positive and significance effect to the employee’s performance of the Jumantono Subdistrict in Karanganyar Regency, (3) Communication has not significantly effect to the employee’s performance of the Jumantono Subdistrict in Karanganyar Regency, (4) Work environment have a positive and significance effect to the employee’s performance of the Jumantono Subdistrict in Karanganyar Regency, (5) Work environment variable have most dominant influence to the employee’s performance. Keywords : leadership, motivation, communication, work environment, the employee’s performance